Analysis of The Effect of Environmental Performance, Company Size, Institutional Ownership and Profitability on Islamic Social Reporting Disclosures - Safira Safira; Putri Nadia Ramadhan (Journal of Islamic Economics and Social Science (JIESS), 2020)
This study aims to obtain empirical evidence of the effect of environmental performance, company size, profitability and institutional ownership on the disclosure of Islamic Social Reporting (ISR). Islamic social reporting (ISR) is still voluntary because there is no standard standard from the government. In contrast to CSR which is mandatory (mandatory). The populations in this study are manufacturing companies in the basic industrial sector and chemicals listed in the Indonesian Sharia Stock Index (ISSI) for the period 2012 - 2015. The next stage is sampling using purposive sampling with sample criteria. The data used is secondary data from the company's financial statements. The design of this research is a causal research with analysis method using multiple linear regressions. The results showed that environmental performance, company size, profitability and institutional ownership had no effect on the disclosure of Islamic Social Reporting (ISR).